Une visite au cimetière arménien d’Addis Abeba. Éléments pour la connaissance d’une diaspora et de ses pratiques funéraires en Éthiopie - Boris Adjemian (Afriques)
By studying places of burial in Addis Ababa, we can ponder the changing situation of Armenian immigrants and their descendants in Ethiopia during the 20th century. The Gulēlē international cemetery provides evidence of the fast growing population of foreigners in the country as of the reign of Menelik II. Its foundation raises questions about how these foreigners were perceived at the time. The funeral practices of Armenian immigrants and their descendants reflect the situation, so hard to understand, of persons who, though considered to be relatively close to Ethiopians, persisted in keeping to themselves as foreigners in the hereafter. This cemetery, the place that best signals the Armenian presence in the country, is a heritage for these immigrants’ descendants who still live in Ethiopia.